Direct Access to Isoindolinone Derivatives by Palladium-Catalyzed C–H Activation and Isocyanide Insertion by Using Molecular Oxygen as the Sole Oxidant - Wang, Dongqi; Cai, Sheng; Ben, Rong; Zhou, Yang; Li, Xingwei; Zhao, Jing; Wei, Wei; Qian, Yong (Synthesis, 2014)
We report a straightforward, aerobic, palladium-catalyzed C–H activation, followed by isocyanide insertion to synthesize isoindolinone derivatives. This transformation is an efficient and step-economic strategy using oxygen as the sole oxidant. We anticipate that this work will inspire in-depth studies as well as versatile applications in various related fields.
Keywords: palladium-catalyzed; C–H activation; isocyanide insertion; isoindolinone; oxygen; heterocycles